Estrutura genética populacional de Stenella clymene (Gray,1850) e sua relação filogenética com o gênero - Nara, Luana Barbosa Carvalho (2015)
The existing information concerning Stenella clymene are scarce specially when considering genetic approaches, which leads to the IUCN red list of threatened species classification as “data deficient”. In many circumstances, molecular studies are difficult as sightings and stranding events are infrequent due the restricted distribution of S. clymene in tropical and temperate deep waters of the Atlantic Ocean. The former studies raised up questions regarding the species position in the genera and a hypothesis that S. clymene has a hybrid origin. The present study analyzed the cytocromo oxidase I (CoI), cytocromo b (Cyt b) and control region (D-loop) of the mitochondrial DNA of northeastern Brazil individuals comparing them with Delphininae sequences obtained from Genbank. Brazilian individuals showed a high genetic diversity and they probably constitute the same population unit. A significant differentiation and high values in the level of FST was found between population units of North Atlantic and South Atlantic Ocean. Between the population units of South Atlantic and Mexican Gulf the differentiation was significant, but FST value was low, in addition the haplotype network and the phylogenetic recovery suggest a connectivity between the two populations. Moreover, in the phylogenetic reconstruction for D-loop region S. clymene is paraphyletic and sister group of Stenella coeruleoalba, Delphinus delphis e Stenella frontalis clade, while for CoI and Cyt b regions S. clymene is polyphyletic and sister group of S. coeruleoalba